2020
DOI: 10.1101/2020.04.07.024455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

JAK1 inhibition blocks lethal sterile immune responses: implications for COVID-19 therapy

Abstract: Cytokine storms are drivers of pathology and mortality in myriad viral infections affecting the human population. In SARS-CoV-2-infected patients, the strength of the cytokine storm has been associated with increased risk of acute respiratory distress syndrome, myocardial damage, and death. However, the therapeutic value of attenuating the cytokine storm in COVID-19 remains to be defined. Here, we report results obtained using a novel mouse model of lethal sterile anti-viral immune responses. Using a mouse mod… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Unfortunately, global and protein-specific surface glycosylation profiling is still challenging but could become an important future avenue to understand better how complex glycan patterns both of the virus as well as host cells determine the tropism of SARS-CoV-2. A rapidly rising number of reports on SARS-CoV-2 implicate intracellular phosphorylation events in a plethora of pathways from growth factor signaling to interferons and interleukins, HIF1A/mTOR signaling, PIKFYVE kinase inhibition, and JAK1 signaling ( 39 , 64 , 65 , 66 , 67 , 68 , 69 ), many of which are implicated in innate immunity. The full extent of phosphorylation regulation (or other PTMs for that matter) by SARS-CoV-2 remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, global and protein-specific surface glycosylation profiling is still challenging but could become an important future avenue to understand better how complex glycan patterns both of the virus as well as host cells determine the tropism of SARS-CoV-2. A rapidly rising number of reports on SARS-CoV-2 implicate intracellular phosphorylation events in a plethora of pathways from growth factor signaling to interferons and interleukins, HIF1A/mTOR signaling, PIKFYVE kinase inhibition, and JAK1 signaling ( 39 , 64 , 65 , 66 , 67 , 68 , 69 ), many of which are implicated in innate immunity. The full extent of phosphorylation regulation (or other PTMs for that matter) by SARS-CoV-2 remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, the IFN response, which is crucial for escalating antiviral responses, besides driving and amplifying the cytokine storm, is vigorous in people with DS [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have showed in DS the occurrence of an interferonopathyc signature with a dysregulation of IFN-inducible cytokines causing a chronic inflammation state Sullivan et al, 2016 , Sullivan et al, 2017 , and a widespread hypersensitivity to IFN stimulation across the human immune system [Araya et al, 2019] . Recently, in an animal model carrying triplication of these IFN receptors, activation of toll-like receptors and consequent induction of the IFN antiviral response, lead to a cytokine storm with a worsening of liver pathology and rapid death [Tuttle et al, 2020] ( Fig. 1 ).…”
Section: Discussionmentioning
confidence: 99%